STRATEGI PENINGKATAN LITERASI DIGITAL DALAM PEMBELAJARAN MATEMATIKA (Studi Kasus Peserta Didik SMAN 1 Tanjunganom Nganjuk) - Widianti, Heni (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
The world community has entered the era of industry 4.0 and has had an impact on human dependence on the use of information and communication technology, in Indonesia based on the survey results show that the Indonesian people are dependent on the use of technology, especially those aged 18-40 years, they spend an average of time using internet with various devices up to 8 hours 36 minutes, but another fact shows that the Indonesian people, including school age, do not yet have digital literacy skills. Therefore, this study aims to examine strategies for increasing digital literacy in mathematics learning at State Senior High School 1 Tanjunganom Nganjuk. The results of this study indicate that first, digital literacy in mathematics learning at State Senior High School 1 Tanjunganom can improve and improve the mathematics learning process, and also to support government programs and school programs in developing digital literacy movements in the digital era, as well as to improve digital literacy skills by use existing facilities and infrastructure. Second, the Literacy Improvement Strategies used include; Strengthening character and responsibility in the use of digital media as a means of learning Mathematics, by strengthening character and responsibility, providing an understanding of the importance of digital literacy in mathematics learning, habituation of the use and utilization of digital media for the learning process, preparing learning links, and using applications -inside application learning.